What were they thinking? Factors influencing police recruits' decisions about force. (24th July 2019) - Hine, Kelly A.; Porter, Louise E.; Westera, Nina J.; Alpert, Geoffrey P.; Allen, Andrea
ABSTRACT: Police officers are increasingly called upon to explain and defend their behaviour towards citizens, particularly where force is used. While there is a well-established body of research on factors that are associated with the use of police force, little is known about whether officers are actually considering these factors when making force decisions. This study takes a naturalistic decision-making approach to examine police decisions in the interactive and dynamic environment of police scenario-based training. It is one of the first studies to explore the range of factors that police assess, and the evaluative ways that they use these factors to make decisions about whether to use force and how much to use. The sample consisted of 91 police recruits at the end of their training. Immediately after participating in a scenario-based training exercise, the recruits discussed their performance and decisions about force with a trainer. These debriefs were recorded and content analysed. Results show that recruits were considering a range of situation and suspect factors in their force decisions. Moreover, recruits were using these factors to assess the threat level of the encounter as well as the suitability of force types in the situation. These findings provide insights into both the specific factors and broad themes of officers' decision-making regarding force. This has implications for understanding force decisions of officers in the field as well as policy implications for force guidelines and models.